Physical property differences of source rocks in the Lucaogou Formation and adsorption ability variation under their influence - Ge, Dongfeng; Lv, Dawei; Yao, Peng; Wen, Shupeng; Li, Jiahui; Lei, Guoming (Frontiers in Earth Science, 2023)
Shale gas exploration is very important for the China in the further. There are many findings of shale gas in Northwest China, especially in Junggar Basin Permian Lucaogou Formation of the Xinjiang Uygur Autonomous Region. However the basic geological characteristics of Lucaogou Formation is not still clear. In order to solve this problems, Quanzijie shale gas collected from the southern margin of the Junggar Basin is taken as the study area, and shale gas resources are investigated and evaluated using the organic-rich shale section. On this basis, the investigation and evaluation of shale gas resources in the Lucaogou Formation is performed. The reservoir performance, preservation conditions, compressibility, and gas-bearing properties of gas-bearing shale intervals are identified. The results are as follows: The vertical and horizontal lithological and lithofacies variations of the source rocks of the Lucaogou Formation are clarified. This layer is characterized by the upward thinning of grain size and the upward darkening of color in the vertical direction. The layer can be divided into upper and middle-lower sections, with organic shale being most developed in the upper section, and sandstone and dolomite being more developed in the middle and lower area. The main hydrocarbon source rocks are developed in the upper area of the Lucaogou Formation. The total thickness of the hydrocarbon source rocks is 78.12–513.73 m. The lithology is mainly gray-black shale, silty mudstone, and oil shale. The average organic carbon content is 4.86%. The maturity of the organic matter is mainly 0.7–0.8%. The shale reservoirs have a high content of brittle minerals, but the physical properties both of the shale and sandstone reservoirs are poor. These are generally ultra-low porosity and ultra-low permeability reservoirs, in which the oil and gas reservoir space is mainly fractures.